The Legal Politics Behind Amendments to The SOE Law and The Institutional Reconstruction of SOEs After Danantara - Retno Meilani; Vina Hardyana Infantri (Universitas Muhammadiyah Malang, 2026)
This study analyzes the legal-political dynamics underlying the amendments to the State-Owned Enterprises (SOE) Law through Law No. 1 of 2025 and Law No. 16 of 2025, as well as their implications for SOE restructuring. This regulatory transformation is not merely an update of norms or a change in nomenclature but reflects the state’s strategic choices in shaping the role, policy direction, and relationship between public power, market mechanisms, and the public interest. The study’s findings indicate that the concentration of authority within Danantara enhances operational efficiency and investment coordination, yet also poses serious risks to democratic accountability, transparency, and checks-and-balances mechanisms. The relatively closed institutional design and reduced legislative oversight open the door to the potential for elite capture, moral hazard, and the marginalization of public control. This shift marks a redefinition of the constitutional role of SOEs, which were originally state instruments to control vital production sectors but are now adapting to corporate investment logic and strategies. This study makes an important contribution to understanding the implications of the formation of a superholding company on SOE governance, including the distribution of authority, the effectiveness of oversight, and the sustainability of the constitutional mandate. Thus, this study is not only academically relevant but also strategically important in ensuring that the transformation of SOEs remains within the framework of the law, democracy, and the public interest.